PHM-Ethics and ETICA: complementary approaches to ethical assessment - Mittelstadt, B; Stahl, B; Fairweather, B (IOS Press, 2013)
The chapter undertakes a comparison of different approaches to the ethical assessment of novel technologies by looking at two recent research projects. ETICA was a FP7 sister project to PHM-Ethics, responsible for identification and ethical evaluation of information and communication technologies emerging in the next 10-15 years. The aims, methods, outcomes and recommendations of ETICA are compared to those of PHM-Ethics, with identification of linkages and similar findings. A relationship is identified between the two projects, in which the assessment methodologies developed in the projects are shown to operate at separate, but complementary levels. ETICA sought to reform EU ethics governance for emerging ICTs. The outcomes of PHM-Ethics are analyzed within the policy recommendations of ETICA, which demonstrate how the PHM-Ethics toolbox can contribute to ethics governance reform and context-sensitive ethical assessment of the sort called for by ETICA.